A mutant-cell library for systematic analysis of heparan sulfate structure–function relationships. (November 2018) - Qiu, Hong; Shi, Songshan; Yue, Jingwen; Xin, Meng; Nairn, Alison; Lin, Lei; Liu, Xinyue; Li, Guoyun; Archer-Hartmann, Stephanie; Rosa, Mitche; Galizzi, Melina; Wang, Shunchun; et al.
Abstract Heparan sulfate (HS) is a complex linear polysaccharide that modulates a wide range of biological functions. Elucidating the structure–function relationship of HS has been challenging. Here we report the generation of an HS-mutant mouse lung endothelial cell library by systematic deletion of HS genes expressed in the cell. We used this library to (1) determine that the strictly defined fine structure of HS, not its overall degree of sulfation, is more important for FGF2–FGFR1 signaling; (2) define the epitope features of commonly used anti-HS phage display antibodies; and (3) delineate the fine inter-regulation networks by which HS genes modify HS and chain length in mammalian cells at a cell-type-specific level. Our mutant-cell library will allow robust and systematic interrogation of the roles and related structures of HS in a cellular context. A library of mutant mouse lung endothelial cells expressing a comprehensive repertoire of heparin sulfate structure modifications enables studies of the structure–function relationships of this complex polysaccharide.